Analisis Sistem Pengendalian Intern terhadap Pengeluaran Kas Tahun 2015-2019 pada Business Center SMK Negeri 2 Mataram - Elok Aulia Rizqi Maligan; Syarifah Massuki Fitri; Vindha Efrin (BADAN PENERBIT STIEPARI PRESS, 2022)
The internal control system is a set of policies and procedures to protect the assets or assets of the company from all forms of abuse, to ensure the availability of accurate company accounting information, and to ensure that all legal provisions (regulations) and management policies have been complied with or carried out properly. by all company employees. The purpose of this study was to determine whether the internal control system for cash disbursements in 2015-2019 at the Business Center of SMK Negeri 2 Mataram was running well. This type of research is descriptive quantitative. Data collection techniques used are documentation studies (documentation), observation and interviews (Interview). The sample in this study amounted to 60 samples. The sampling method in this study uses Simple Random Sampling and data analysis techniques using the SPSS version 16.0 program. The results of this study indicate that the internal control system for cash disbursements in 2015-2019 at the Business Center of SMK Negeri 2 Mataram has fulfilled the elements of the internal control system. From the results of t count is greater than t table that is 30.60 > 2.002 means that H0 is rejected and Ha is accepted. this shows that the internal control system in the Business Center of SMK Negeri 2 Mataram has a positive and significant influence on cash disbursements. The independent variable of the internal control system is 94.2%. While the remaining 5.8% is explained by other variables that are not part of this study.